Examining the impacts of individual lot stormwater detention in a housing estate - Mah D.Y.S.; Ngu J.O.K.; Caroline P.D.; Malek M.A. (Khon Kaen University,Research and Technology Transfer Affairs Division, 2023)
This paper describes the Storm Water Management Model (SWMM) simulations of three individual lot stormwater detention systems under the car porches of houses. These three systems consist of ready-made modular units presumably fitted under 49 m2 car porches of 204 double-story terrace houses. The 37,032 m2 housing estate is calculated to have 75% of land covered with houses, 25% with roads and other infrastructures. The housing estate was subjected to 5-minute, 10-year Average Recurrent Interval (ARI) short-duration design rainfall. The model predicted that all three systems could reduce the peak runoff at outfall from 2.79 to 0.38 m3/s. It indicated that any of the system could cause 86% reduction of the runoff for the whole housing estate. In order to differentiate the performance of the three systems, the housing lot was further investigated. When Type 1 system (1.15 m high with 49 m3 per lot) was analysed by the SWMM model, only 8% of its storage volume was filled that highlights an over design. Type 2 system (0.3 m high with 6 m3 per lot) modelled at 84% while Type 3 system (0.3 m high with 9 m3 per lot), at 54%. The difference in heights between the systems explained the low percentage of filling for the Type 1 system. Comparing Type 2 and Type 3, concrete structure within Type 3 had only half of its volume filled. In this light, the Type 2 system made of polyethylene pieces was found the most efficient in lowering post-development peak runoff. 2022, Khon Kaen University,Research and Technology Transfer Affairs Division. All rights reserved.